SOSIALISASI PENGELOLAAN SAMPAH MELALUI PEMBERDAYAAN PERAN IBU-IBU PKK DI DESA MURTAJIH KECAMATAN PADEMAWU KABUPATEN PAMEKASAN - Adriansyah, Agus Aan; Firdausi, Nurul Jannatul; Sa’adah, Nikmatus; Arifah, Ika Fahraeni; Sanila, Halimatus; Sulistianah, Renjani; Puspitasari, Megaratri (Perkumpulan Legowo Cerdas Sejahtera, 2023)
Until now Murtajih village does not yet have a communal landfill. Waste disposal is carried out in open land by being piled or burned because the community is not accustomed to sorting garbage. Therefore, socialization about waste management is needed to reduce the amount of waste, increase creativity and public welfare. The expected outcome is to increase community understanding and creative ideas emerge in creating economically valuable waste products. Service starts by surveying the target group, preparing infrastructure and infrastructure, action and evaluation. The action reviews the community's initial knowledge, dissemination of waste management through PowerPoint media, videos and simulations of waste bank management, and understanding of community knowledge after the intervention. Final evaluation by comparing the value of pretest and posttest using the Wilcoxon-test. The socialization was carried out with counselling on the target to increase public understanding and concern in waste management. Socialization was given through exposure material, video management and waste management practices targeting PKK mothers. Early identification shows that community knowledge is still not good, whereas after socialization it has become better. The community has the initiative to make a garbage bank administrator. This activity indicates the importance of socialization in increasing public knowledge and awareness of waste management.